2015
DOI: 10.1016/j.ascom.2015.09.001
|View full text |Cite
|
Sign up to set email alerts
|

cosmoabc: Likelihood-free inference via Population Monte Carlo Approximate Bayesian Computation

Abstract: Approximate Bayesian Computation (ABC) enables parameter inference for complex physical systems in cases where the true likelihood function is unknown, unavailable, or computationally too expensive. It relies on the forward simulation of mock data and comparison between observed and synthetic catalogues. Here we present cosmoabc, a Python ABC sampler featuring a Population Monte Carlo variation of the original ABC algorithm, which uses an adaptive importance sampling scheme. The code is very flexible and can b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
101
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(102 citation statements)
references
References 49 publications
1
101
0
Order By: Relevance
“…Until now, ABC seems to already have various applications in biology-related domains (e.g., Beaumont et al 2009;Berger et al 2010;Csilléry et al 2010;Drovandi & Pettitt 2011), while applications for astronomical purposes are few: morphological transformation of galaxies (Cameron & Pettitt 2012), cosmological parameter inference using type Ia supernovae (Weyant et al 2013), constraints of the disk formation of the Milky Way (Robin et al 2014), and strong lensing properties of galaxy clusters (Killedar et al 2015). Very recently, two papers (Ishida et al 2015;Akeret et al 2015) dedicated to ABC in a general cosmological context have been submitted.…”
Section: Introductionmentioning
confidence: 99%
“…Until now, ABC seems to already have various applications in biology-related domains (e.g., Beaumont et al 2009;Berger et al 2010;Csilléry et al 2010;Drovandi & Pettitt 2011), while applications for astronomical purposes are few: morphological transformation of galaxies (Cameron & Pettitt 2012), cosmological parameter inference using type Ia supernovae (Weyant et al 2013), constraints of the disk formation of the Milky Way (Robin et al 2014), and strong lensing properties of galaxy clusters (Killedar et al 2015). Very recently, two papers (Ishida et al 2015;Akeret et al 2015) dedicated to ABC in a general cosmological context have been submitted.…”
Section: Introductionmentioning
confidence: 99%
“…Lin & Kilbinger (2015b) and Lin et al (2016) showed that ABC is an efficient and successful parameter inference strategy for WL peak count analyses. The method has also been used recently in several other astrophysical and cosmological applications (Cameron & Pettitt 2012;Weyant et al 2013;Robin et al 2014;Killedar et al 2015;Ishida et al 2015;Akeret et al 2015). We constrain the parameter set (Ω m , σ 8 , w We implement a population Monte Carlo (PMC) ABC algorithm to iteratively converge on the posterior distribution of parameters.…”
Section: Parameter Inference With Approximate Bayesian Computationmentioning
confidence: 99%
“…Finally Hahn et al (2017) demonstrate the feasibility of using ABC to constrain the relationship between galaxies and their dark matter halo. The recent birth of Python packages providing sampling algorithms in an ABC framework, such as astroABC (Jennings & Madigan 2017) and ELFI (Kangasrääsiö et al 2016), which implement SMC methods, and COSMOABC (Ishida et al 2015) which implements the PMC algorithm, will probably facilitate the rise of likelihood-free inference techniques in the astronomical community.…”
Section: Introductionmentioning
confidence: 99%